The Financing Problems Facing the Agricultural Sector in Nigeria and the Prospect of Waqf-Muzaraah-Supply Chain Model (WMSCM) - Oladokun Nafiu Olaniyi; Mohamad Asmy Bin Mohd Thas Thaker; Hassanudin Mohd Thas Thaker; Anwar Allah Pitchay (Global Review of Islamic Economics and Business, 2014)
Agriculture sector becomes important sector in many developing countries including in Nigeria. The contribution of agricultural sector to the development of Nigeria is considerable. This important sector was the economic backbone upon which the government of the Federal Republic of Nigeria relied for its foreign exchange and revenue. A country was once a net exporter of agricultural products. However, since the discovery of oil in the early 1960, agricultural productivity has continually decreased due to many problems, especially related to financial aspect. Several programmes and policies have been adopted by various administrations to find solution to the dwindling agricultural productivity but to no avail. These solutions have mainly focused on alleviating the financial problems the farmers face. Usually financial intermediaries including banks would provide micro-financing to the farmers but with high interest rates coupled with collateral requirements. Hence, this mode of financing has not produced any significant result. This study will therefore examine problems facing agricultural sector in Nigeria with special emphasis on its financial aspect and propose a Waqf-MuzaraahSupply Chain model (WMSCM). Under this model, Waqf fund will be used for providing financial facility of the farmers. The relationship between farmers and financial institutions is based on partnership where profit and loss will be shared by both parties. This will enhance commitment by and cooperation among both parties to ensure the success of the business. Furthermore, the issues of collateral and high interest rate that constrain the financial ability of the farmers and their agricultural output are inherently solved by the model. Moreover, the model has features of investment and risk diversification for both the financial institutions and the farmers that will lead to high agricultural productivity and employment generation in the economy.